Respuesta :

Answer:

y = - 2(x + 4)² + 6

Step-by-step explanation:

The equation of a parabola in vertex form is

y = a(x - h)² + k

where (h, k) are the coordinates of the vertex and a is a multiplier

Here (h, k ) = (- 4, 6 ) , thus

y = a(x - (- 4) )² + 6 , that is

y = a(x + 4)² + 6

To find a substitute (- 2, - 2) into the equation

- 2 = a(- 2 + 4)² + 6 ( subtract 6 from both sides )

- 8 = a(2)² = 4a ( divide both sides by 4 )

- 2 = a , thus

y = - 2(x + 4)² + 6 ← equation in vertex form